Aptid??o f??sica, perfil antropom??trico e biodisponibilidade do ??xido n??trico como preditores de hiper-reatividade press??rica em escolares filhos de normotensos e hipertensos - Oliveira, Jos?? Fernando de (2016)
Systemic arterial hypertension is a global health problem, affecting even the adolescent population, in this age group, genetic predisposition and biopsychosocial modifications are important factors in the development of hypertension. However, few studies have analyzed and associated the combination of family history, physical activity level, anthropometric profile and physical fitness on blood pressure reactivity and nitric oxide bioavailability in adolescents submitted to the Shuttle Run 20 meters, Cold Pressor Test and palmar grip strength. A total of 172 adolescents (n = 60???, n = 112???), high school students of the Technical College of Campinas-SP, aged 14 to 18 years, were classified into: normotensive children (FN; = 38???, n = 48???) and hypertensive children (FH; n = 22???; n = 64???), subdivided into active and sedentary. All procedures followed the ethical requirements of resolution 466/12 of the National Health Council. The results showed significant differences between FN vs. FH in several parameters of physical fitness, hemodynamic components and in salivary nitrite. Therefore, this study demonstrated that FH adolescents already present a negative influence of anthropometric, cardiovascular and physical activity levels on the bioavailability of salivary nitric oxide in children of hypertensive patients.